Cinnamon – Differentiation of Four Species by Linking Classical Botany to an Automated Chromatographic Authentication System. (23rd November 2019) - Ford, Paul W; Harmon, Alan D; Tucker, Arthur O; Sasser, Myron; Jackoway, Gary; Albornoz, Gerardo; Grypa, Roman D; Pratt, Jonna L; Cardellina, John H
Abstract: One of the world's oldest spices, cinnamonis also one of the most popular. Species of the genus Cinnamomum offer a variety of extractable oils with aroma and flavor characteristicsof importance to the flavor industry, so differentiating cinnamon samples for culinary-based applicationsis very important. Cinnamon also has reported healthbenefits associated with specific phytochemical constituents, but its composition can vary greatly depending on species and source region. A substantial amount of the research reported on cinnamon does notprovide thorough documentation of the source and taxonomic identification of the study material, a very common issue with studies of food and medicinal plants.In the interest of providing some clarity to the discussion of the health benefits and culinary attributes of the different cinnamon types in the marketplace, we offer the results of a long-term chemotaxonomic study of cinnamon samples sourced from different regions of the world and link those chemical data to classical taxonomic identification of the source plants. We provide details of the effective use of an automated chemotaxonomic analytical method to differentiate cinnamons from various geographic regions. Also included are chromatographic data for the polyphenolic/procyanidin fractions of each species, as cinnamon type-A procyanidins are often the purported source of biological activity in cinnamon and cinnamon extracts.